Implementasi Project Picture Review Pada Pembelajaran Matematika Di Kota Banjarbaru - Istikamah; Darmiyati (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2024)
The purpose of this study was to describe the activities of educators, to analyze the activities and learning outcomes of students on flat shape material in grade 4 SDN 5 Guntung Manggis Banjarbaru. The approach used in this study is a qualitative and quantitative approach with the type of Classroom Action Research (PTK) which is carried out in four meetings. The research setting was carried out at SDN 5 Guntung Manggis Banjarbaru for grade 4 students with a total of 20 students for the 2022/2023 academic year. Data analysis is calculated based on the percentage scale and learning mastery indicators that have been determined. The results showed that the activity of educators at the fourth meeting reached the "Very Good" criteria. The activity of the fourth meeting students reached the "Very Active" criteria. The classical completeness of the learning outcomes of students at the fourth meeting has achieved classical completeness. Based on these findings it can be concluded that this model can increase the activity and results of learning mathematics in flat shape material for students in grade 4 SDN 5 Guntung Manggis Banjarbaru. The suggestion put forward by the researcher is that the use of this model can be an alternative and a contribution for educators to improve the learning process.